Home School Reading and Study Guides: The New Book of Knowledge - Gillespie, John T. and Christine B. Gilbert (Grolier Incorporated, 1988)
The Home And School Reading Guide is a selected list of books for children at all reading levels. It is a source for books will supplement the information contained in The New Book Of Knowledge. It will also suggest books that answer the needs and interests of children. Every effort was made to include in this Guide recently published titles that reflect the trend, development, and activities of todays rapidly changing world.
Keywords: Education